Perhitungan Jarak Dalam Meminimalkan Biaya Perjalanan Menggunakan Algoritma Generate And Test - M, Padma Mike Putri (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2024)
Generate and Test is included in the artificial intelligence section where the search process must find a solution to the success of a system in producing value. Generate and test is a simple method in the heuristic search process. The way this algorithm works is like a combination of depth-first search and backtracking because the solution must be generated completely before being tested. If the generation of a solution is done systematically and follows the procedure, it will find the solution. The problem in this research is determining a route that is difficult to detect because it has many paths to get to the final value, so an algorithm is needed to solve this problem so that the path to be taken has a smaller range and is able to manage time and costs. Based on the final results obtained, 3 paths were found that can be used as a reference in saving time and costs, including, path 1 f (E-F-L-R-U-Z) = 9+6+13+16+13=57, path 2. f (E-G-M-S-X-Z = 7+5+ 11+19+12 =54 and path 3. f (E-H-N-T-Y-Z = 5+9+8+14+16=52. This algorithm can be used as a reference in determining travel routes and other measurement cases.